2014
DOI: 10.1186/bf03353079
|View full text |Cite
|
Sign up to set email alerts
|

A new view of earthquake and volcano precursors

Abstract: A close coupling between monitoring and modeling is needed for a quantitative prediction of volcanic eruption and earthquake occurrence. The need is demonstrated for the volcano, Piton de la Fournaise, for which a relatively simple model can be constructed because of the isolated tectonic setting and can be tested in a short time because of the high rate of eruptions. Our conceptual model (Fig. 2) explains various observations for each of the 49 eruptions since 1972 in terms of the varying conditions of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 43 publications
2
14
0
1
Order By: Relevance
“…This is consistent with the brittle-ductile interaction hypothesis of earthquake loading by plate-driving forces proposed by Aki (2004) on the basis of three independent studies; global study of tectonic stress by Zoback and Zoback (2002), regional study of Iio et al (2002Iio et al ( , 2004, and the observed correlation between coda Q and N (M c ) by Jin andAki (1989, 1993). The occurrence of the Mw 6.8 central Niigata earthquake within the NKTZ in 2004 encourages further studies along this line.…”
Section: Conclusion Remarkssupporting
confidence: 76%
See 2 more Smart Citations
“…This is consistent with the brittle-ductile interaction hypothesis of earthquake loading by plate-driving forces proposed by Aki (2004) on the basis of three independent studies; global study of tectonic stress by Zoback and Zoback (2002), regional study of Iio et al (2002Iio et al ( , 2004, and the observed correlation between coda Q and N (M c ) by Jin andAki (1989, 1993). The occurrence of the Mw 6.8 central Niigata earthquake within the NKTZ in 2004 encourages further studies along this line.…”
Section: Conclusion Remarkssupporting
confidence: 76%
“…Recently, Aki (2004) noticed that the simultaneous positive correlation between Q −1 c and N (M c ) obtained for the 50 year-period by Jin andAki (1989, 1993) for California, was disturbed for several years before the 1952 M7.5 earthquake, Kern County, California and the 1989 M7.1 earthquake, Loma Prieta, California. Jin et al (2004) extended the analyses of temporal variation of coda Q −1 and N (M c ) for central and southern California and applied a 10-year moving time window to calculate the cross-correlation between Q −1 c and N (M c ).…”
Section: The Spatial Distribution Of N (M C )mentioning
confidence: 99%
See 1 more Smart Citation
“…Some papers reported anomalous value of Q c around volcanoes, faults 5) , which means the media has anomalous inhomogeneity. Also the recent results 4) reported that anomalous value of Q c was detected after a large earthquake. These results suggest that the order of inhomogeneities may vary in the course of long-term earthquake generation cycle, i.e., before and after the failure of crustal material takes place.…”
Section: Introductionmentioning
confidence: 99%
“…The cracks opened or closed by the stress change are one of the major factors which change the property of the crust. Jin et al (2004) 3) and Aki (2004) 4) proposed a "Brittle-Ductile Hypothesis" after a long-term observation of the seismicity around the San Andreas Fault that has led them to find a high correlation with Q c .…”
Section: Introductionmentioning
confidence: 99%